Caracterización del Servicio de Alojamiento Estudiantil Prestado en Lugares Acondicionados en la Ciudad de Bogotá, Localidad de Teusaquillo Chapinero - Barbosa Parra, Mateo (Universidad Antonio Nariño, 2023)
Due to the lack of infrastructure available for foreign students in Bogotá, particularly in the localities of Chapinero and Teusaquillo, homeowners adapt their homes and provide a university lodging service, where in many cases they are places with environments that are not appropriate for a good development. academic.